Análise molecular da adaptação de insetos herbívoros aos cardenolídeos de calotropis procera: aspectos bioquímicos e ecológicos - Freitas, Larissa Barbosa Nogueira (2019)
The plant Calotropis procera synthesizes a variety of secondary metabolites, such as cardenolides, a type of toxic metabolite of defense against herbivores. Thirty-five cardenolides have already been identified in C. procera and had their molecular structure resolved. Cardenolides are toxic by inhibiting the enzymatic activity of ATPases of Na+/K+, causing cell death. However, herbivorous insects Danaus plexippus (Lepidoptera), Oncopeltus fasciatus and Aphis nerii (Hemiptera) are capable of using C. procera as host. Why does the plant synthesize a variety of cardenolides? Which are the structural and chemical characteristics of these molecules? How do these herbivores prevent the action of these metabolites? In this work, the C. procera cardenolides were classified in three groups, one of them with three subgroups, according to their structural characteristics. The hydropaticity index was defined through the partition coefficient log (Log P). Three-dimensional (3D) models of the ATPα1 of Na+/K+ from D. plexippus, O. fasciatus and A. nerii were constructed through comparative modeling using the SWISS-MODEL and Phyre2 servers, and were subsequently validated and refined. After refinement, the 3D structures were validated again. The binding site of cardenolides in the 3D structures of these three enzymes was identified and analyzed. With the aid of structural data described in the literature about the binding of ouabain (the most commonly used cardenolides for toxicity studies) in ATPα1 of Na+/K+, it was proposed that the resistance of D. plexippus, O. fasciatus, and A. nerii to the toxic effects of C. procera cardenolides is also related to amino acid substitutions with different chemical properties in specific enzyme sites. Probably, substitutions in positions 104, 115 and 302 have the higher effect on the increased insensitivity of the ATPα1 of Na+/K+ of these herbivores to cardenolides. Through molecular docking of the 3D structures of these ATPα1 of Na+/K+ with the cardenolides from C. procera was possible to establish a relationship between the specificity of polarity of the cardenolides sequestered by these herbivores and the selectivity of these metabolites about their ATPα1 of Na+/K+. Therefore, it is presumable that cardenolides that are not sequestered by these herbivores can bind in active site of their ATPα1 of Na+/K+, thus the selectivity of these metabolites to these enzymes is directly related to their polarity. It is concluded that C. procera diversifies the cardenolides structure in an attempt to any of them can interact with ATPα1 of Na+/K+ of the herbivores and promote their chemical defense. Insects, in turn, achieve the resistance excluding potentially toxic cardenolides from their bodies and sequestering those that are not selective for them or modifying the structure of the cardenolides, although this latter strategy is not metabolically known.